The effect of social suspicion on social media addiction among Chinese college students: A moderated mediation model - Tao Wei; Xiao-Li Xing; Jing-Jing Liu; Yan Gan; Xue Gong; Xiu-Fang Zhang; Bu Xu; Xiang-Xia Rong (PLoS ONE, 2025)
Objective This study investigates the impact of social suspicion on social media addiction among Chinese college students, examining the mediating role of the sense of meaning in life and the moderating effect of gender. Methods A cross-sectional survey was conducted from September 19, 2023, to November 2, 2023, involving 1,558 students from three universities in southern Anhui Province, China. Participants completed questionnaires assessing social suspicion, social media addiction, and the sense of meaning in life. Data were analyzed using correlation analysis, Hayes’ PROCESS macro, and bootstrap methods to test mediation and moderation effects. Results The findings revealed a bidirectional relationship between social suspicion and social media addiction. Social suspicion positively predicted social media addiction, with the sense of meaning in life mediating this relationship. Gender moderated the mediating effect, as the indirect effect of social suspicion on social media addiction through the sense of meaning in life was significantly stronger among female students compared to male students. Additionally, social media addiction also positively predicted social suspicion, with the sense of meaning in life and gender moderating this relationship. Conclusion This study reveals a bidirectional relationship between social suspicion and social media addiction among Chinese college students, mediated by a sense of meaning in life and moderated by gender. Social suspicion directly drives addiction while indirectly exacerbating it through reduced the sense of meaning in life, with females showing stronger mediation effects and males exhibiting heightened susceptibility to suspicion when addicted. These findings emphasize the need for gender-tailored interventions to address psychological vulnerabilities and mitigate risks of digital overuse.